ANALISIS YURIDIS DAN EMPIRIS TERHADAP IMPLEMENTASI OTONOMI DAERAH DI INDONESIA - Zudan Arif Fakrulloh (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2003)
To implement the district autonomy is basically the same as to build the existence of democracy. Various factor and variables can be affected its success, especially whenever central and local government, each of which that should take every effort to reach the same perception and the same contain of district autonomy, added by goodwill of every government and bureaucrat for the sake of Indonesian people welfare and the wholeness of Republic of Indonesia.